مساهمة الوكالة الوطنية للنفايات في تعزيز الإنتقال نحو الإقتصاد الدائري - دهيمي ،جابر (جامعة الوادي University of Eloued, 2025)
يهدف موضوع بحثنا إلى ابراز دور الاقتصاد الدائري كتوجه حديث تسعى من خلاله الدول والمنظمات إلى الاستفادة من النفايات وتثمينها، بعدما صارت مشكلا تواجهه الدول خصوصا مع النمو الصناعي والسكاني المتزايد، وقد سعت الوكالة الوطنية للنفايات إلى المساهمة في تفعيل آليات الإقتصاد الدائري بتقديمها لمبادرات عديدة، وكذا انخراطها في سياسات مختلفة بهدف معالجة التأثيرات السلبية للنفايات. توصلت الدراسة إلى أنه بالرغم من الجهود المختلفة للوكالة في سبيل معالجة وفرز النفايات وتثمينها اقتصاديا، إلا أن قلة توعية وتحسيس المواطنين بأهمية الفرز، جعل مسار تدوير النفايات يشهد صعوبات وجب تصحيحها بالتكوين والتوعية للمنظمات والمواطنين. This paper aims to examine the role of circular economy as a modern orientation through which States and organizations seek to utilize and value waste. It has become a problem for States, especially with increasing industrial and population growth. The National Waste Agency has sought to contribute to the operationalization of circular economy mechanisms by providing them with various initiatives, as well as engaging in various policies to address the negative impacts of waste. The study found that despite the Agency's various efforts to process, sort and value waste economically, the lack of awareness and awareness among citizens of the importance of screening made the waste recycling trajectory difficult and needed to be corrected by composition and awareness among organizations and citizens .
National Waste Agency's contribution to promoting the transition to a circular economy
Keywords: تلوث; نفايات; اقتصاد دائري; وكالة وطنية للنفايات; Pollution; Waste; Circular economy; National Waste Agency